2018
DOI: 10.1055/s-0038-1668144
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogenic Necrotizing Enterocolitis: A Clinically Distinct Entity from Classical Necrotizing Enterocolitis

Abstract: This is the first evidence-based study showing that infants with cardiogenic NEC have different demographics and outcomes than those with classical NEC. The risk of developing NEC and the mortality rate are higher among infants with CHD than in those without. Conversely, the need for intestinal surgery is lower in babies with cardiogenic NEC than in those with classical NEC. Further studies are needed to establish preventative and management interventions that are specific to infants with or at risk of develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 82 publications
4
40
0
2
Order By: Relevance
“…Previous studies have demonstrated the association of NEC with CHD, presenting controversial results on incidence, associations, and mortality (3,8,10,(13)(14)(15)(16) with various population sizes and subgroup analyses. Siano et al (8) reported that congenital heart defects could be identified as a risk factor for the incidence of NEC (OR 1.849) and increased mortality rates (OR 3.4). Lau et al (16) associated patients with ductal dependent congenital heart disease with an elevated risk of NEC compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the association of NEC with CHD, presenting controversial results on incidence, associations, and mortality (3,8,10,(13)(14)(15)(16) with various population sizes and subgroup analyses. Siano et al (8) reported that congenital heart defects could be identified as a risk factor for the incidence of NEC (OR 1.849) and increased mortality rates (OR 3.4). Lau et al (16) associated patients with ductal dependent congenital heart disease with an elevated risk of NEC compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes by baseline elevation of circulating endotoxin and proinflammatory cytokines (e.g., sepsis, systemic inflammation, shock) are the possible cause of further injuries, such as bowel necrosis. In recent research, separation of pathophysiology, incidence, and mortality of NEC in CHD patients and NEC in preterm infants was brought into focus (8)(9)(10). Accordingly, impaired intestinal perfusion and reduced intestinal arterial oxygen saturation in infants with cyanotic heart disease outrank classical causes in pathogenesis and are the leading causes for its development and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Major risk factors include preterm birth, low birthweight, congenital cardiac anomalies, and formula-feeding. [5][6][7] Initiatives to reduce the incidence of NEC have focused on modifiable risk factors with the NEC-zero committee strongly recommending the use of human breast milk and avoidance of antacids. 8 Maximizing the effectiveness of such interventions to reduce the morbidity of NEC, however, requires clinicians to accurately identify those at greatest risk of developing more severe forms of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that oral administration of a dual-strain probiotic might be beneficial to reduce the rate of NEC in infants with aortic arch malformations. The low frequencies of overall and postoperative NEC in our center are rather in the lower range of the various NEC frequencies reported in previous studies, making analyses whether the administration of probiotics has an influence on the frequency of NEC in CHD patients challenging [2, 5, 6].…”
Section: Discussionmentioning
confidence: 92%
“…Presence of a congenital heart disease (CHD), particularly a complex or ductal-dependent CHD, is a major risk factor for the development of NEC in near-term and full-term neonates [2-4]. The incidence of NEC in term infants with CHD has been reported to be 3–11%, which is substantially higher than rates reported for the entire population of late preterm and term newborns [2, 5, 6].…”
Section: Introductionmentioning
confidence: 99%